Case sharing - an approach for improving clinical experience to cases of advanced complexity among undergraduate dental students - Srinivas Sulugodu Ramachandra; Vivek Vijay Gupta; Khairiyah Abd Muttalib (Elsevier, 2021)
Introduction/Problem: Clinical experience in cases of advanced complexity/rare cases is limited among undergraduate dental students. This commentary narrates a module termed "case sharing", wherein a small group of undergraduate dental students treat/assist, document and present advanced or rare cases to their entire cohort in eight weeks. Approach: Undergraduate students perform procedures of straightforward and moderate complexity, and later assisted the clinical specialists during procedures of advanced complexity. students document these cases with clinical photographs and case notes to make presentations that were uploaded in the faculty's online management system to be reviewed by the entire cohort. student groups presented their cases with their entire cohort. an independent assessor assessed the groups for their organization of the case, information collected on the topic, critical analysis of the case, defending the diagnosis and treatment plan, teamwork and presentation skills. Evaluation: Students reported improvement in the depth of knowledge on particular diseases/procedures, a better understanding of holistic management of advanced cases, improved rapport, team spirit and communication among group members. they also reported difficulties in recruiting and completing the procedures within eight weeks. Discussion: Apart from improving the clinical experience of undergraduate students, the module provides an opportunity for the development of teamwork, communication skills, and ethical presentations among students, which are invaluable to the faculty to meet its programme learning outcomes. case sharing provides a platform for holistic learning and serves as an alternative learning method aside from didactic lectures and routine clinical supervision.